The Difference of Effectivity Between Nutmeg Seed Extract (Myristica Fragrans Houtt) and Diazepam Based on Sleep Induction Time on Swiss Webster Mice - Arif Azhari Nasution; Debby Mirani Lubis (Buletin Farmatera, 2020)
According to the National Sleep Foundation in America, more than one third (36%) of young adults aged 18-29 years reported having difficulty getting up early (compared to 20% at 30-64 years old and 9% over 65 years). The National Sleep Foundation also states that in Indonesia the prevalence of insomnia sufferers reaches 70% at least once a week and 30 million people have difficulty sleeping every night. This study is an experimental study with a post-test only control group design. The samples used were 27 male Swiss webster mice which were divided into three groups. The treatment group was given nutmeg seed extract at a dose of 7.5 mg / kgBW; the positive control group was given diazepam, and the negative control group was given aquabidest. The results showed the difference in the average value of sleep induction time in the treatment group was 2.97 minutes, positive control group 5.06 minutes, and negative control group 8.43 minutes with p = 0.00. Conclusion: There is a significant difference between the effectiveness of nutmeg seed extract 7.5 mg / kgBW with diazepam based on the time of sleep induction in Swiss webster male mice.